1999
DOI: 10.1183/09031936.99.13367399
|View full text |Cite
|
Sign up to set email alerts
|

Washing plastic spacers in household detergent reduces electrostatic charge and greatly improves delivery

Abstract: Ionic detergents reduce electrostatic charge on plastic spacers, thereby improving in vitro drug delivery. The aim of this study was to gain practical information on the use of detergents and to evaluate the relevance of this information on in vivo drug deposition. Measurement of electrostatic charge and salbutamol particle size distribution was carried out on detergent-coated and noncoated plastic spacers. The efficiency of four household detergents was compared, and the influence of dilution and the duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 17 publications
6
109
0
9
Order By: Relevance
“…A limpeza da boca após o uso do inalador dosimetrado ou de pó seco também é recomendada com o objetivo de reduzir a biodisponibilidade sistêmica (porção deglutida) 9 . É importante enfatizar as diferenças entre os metabolismos dos diferentes CE.…”
Section: Dose Versus Segurançaunclassified
“…A limpeza da boca após o uso do inalador dosimetrado ou de pó seco também é recomendada com o objetivo de reduzir a biodisponibilidade sistêmica (porção deglutida) 9 . É importante enfatizar as diferenças entre os metabolismos dos diferentes CE.…”
Section: Dose Versus Segurançaunclassified
“…In a review article regarding electrostatics and inhaled medications, 32 the authors suggest that the detergent concentration is not important: that a few drops is all that is needed, which was based on a study by Piérart et al 33 These investigators used a wide range of detergent concentrations and did not find a difference in fine particle delivery. 32,33 Second, should the soap be rinsed off or allowed to remain on the device to reduce the electrostatic charge in the spacer? The literature states the benefit of not rinsing the detergent off after washing and to simply wash in detergent and allow the device to air-dry.…”
Section: Add-on Devices: Pep and Valved Holding Chambersmentioning
confidence: 99%
“…(13, 14) In brief, the spacers were immersed in a solution of two drops of neutral detergent in one liter of water. After 30 min, the devices were left to dry for 24 h in room air, without having previously been rinsed.…”
Section: Resultsmentioning
confidence: 99%
“…(11,12) Studies have reported that static can be eliminated by simple procedures. (13)(14)(15) The objective of the present study was to determine whether the use of inhaled albuterol via an MDI with a large-volume spacer with antistatic treatment modified the bronchodilator 754 Araújo FB, Corrêa RA, Pereira LFF, Silveira CD, Mancuso EV, Rezende NA J Bras Pneumol. 2011;37(6):752-758 the mean FEV 1 prior to bronchodilator use was found to be 2.83 L, whereas the mean FEV 1 after bronchodilator use was found to be 3.05 L. A previous study evaluated the equivalence between two devices for the administration of albuterol to asthma patients, and the weighted mean difference was estimated to be ± 0.25 L. (16) Assuming those values, a type I error of 0.05, a type II error of 0.20, and a minimum detectable difference of 0.125 L between the groups for a two-tailed test, we estimated that the number of patients needed for the study was 24.…”
Section: Introductionmentioning
confidence: 99%